Analisis Peran Komunitas Gubuk Inspirasi Dalam Membantu Mengembangkan Kualitas Pendidikan Dan Skill Pemuda Di Desa Sumberbrantas Kota Batu - Mujtahid; Hasan Assidiqi, Ali; Sadiyah, Dini (CV. SINAR HOWUHOWU, 2025)
This study aims to analyze the role of the Gubuk Inspirasi Community in developing the quality of education and skills of youth in Sumberbrantas Village, Batu City. The background of this study stems from the low access to non-formal education and limited opportunities for self-development for youth in rural areas. This research used a descriptive qualitative approach, with data collection techniques including observation, in-depth interviews, and documentation. The results indicate that Gubuk Inspirasi plays a strategic role in improving literacy, learning motivation, and technical and social skills of youth through programs such as literacy classes, public speaking training, graphic design, and entrepreneurship. The existence of this community creates an alternative learning space that is inclusive, enjoyable, and builds the character of the younger generation. The implications of this study confirm that community-based communities can be significant agents of social change in supporting human resource development at the local level. This study also recommends further quantitative and comparative studies to strengthen the community-based youth empowerment model in other regions.